PKM PELATIHAN PEMASARAN PRODUK KERUPUK IKAN PAYUS UD HIMMAH JAYA SIDOARJO - Michael Ricky Sondak; Pramesti Sanicara; Natalia Christiani; Baswara Yua Kristama (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
Business development in culinary area requires marketing to be well known by customers. Online marketing nowadays can help many small businesses to be well known globally. This community service aims to provide marketing training for fish cracker products at UD Himmah Jaya in Sedati District, Sidoarjo. By implementing this program, UD Himmah Jaya will be able to improve their marketing strategy that has been done so far by utilizing social media. This training provided by highlighting the uniqueness of the product, utilizing the community and connections that have been established so far to be more productive.